PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP PENETRASI PASAR INDUSTRI KECIL MENENGAH KLASTER BATIK DI KOTA SEMARANG - Findri Mustika Sari; Hari Susanta Nugraha (Universitas Diponegoro, 2018)
The problem faced by IKM batik in Semarang City is the weakness of penetration ability of Batik Semarangan style in Semarang City. This can be seen from the low market share in Semarang City, even showing a declining trend from 2012 to 2016. The perceived factor is able to influence the penetration of IKM Batik Semarang market, among others are product quality and brand image. This study was conducted to determine the effect of product quality and brand image on market penetration of Small and Medium Industry (IKM) Batik in Semarang City. In this study using sampling technique sampling census so that can be taken 74 craftsmen Klaster Batik members in the city of Semarang. The data analysis used is regression. The results showed that product quality (X1) has a positive and significant influence on market penetration (Y), brand image (X2) has a positive and significant influence on market penetration (Y). The results also show that there is a positive and significant influence between product quality and brand image together to market penetration.